إعلان القاهرة الفلسطيني نحو تأسيس نظام سياسي جديد : ندوة العدد - 31 - نوفل، أحمد سعيد; غزال، محمد; الحوراني، محمد; الحمد، جواد; البرصان، أحمد سليم (مركز دراسات الشرق الاوسط, 2005)
the Cairo Declaration is an outcome of the A1 Aqsa Intifada which began on 28 September, 2000, and carried the banner of struggle for four years under a national unity slogan. The Cairo Declaration is the first of its kind ever to be made since the establishment of Palestine Liberation Organization (PLO) in 1964. Rebuilding the PLO today is seen as crucial because of the participation of Islamists in the political set up. Hamas has been warning of the backlash if the Parliamentary elections were postponed unilaterally, and therefore saw the Cairo Declaration as one package. Fatah, on the other hand, sees it as a first step to rebuilding the Palestinian political system and warns of Israeli attempts to frustrate such an achievement. These views were presented in an MESJ seminar on 11 April 2005 in which leading figures in Fatah and Hamas as well as three other academics participated in. Participants called on the Palestinian factions to be flexible and put forward different strategic alternatives. Israel is aware that Hamas can control the Palestinian political system in any election, and therefore has pushed to postpone the polls. The Islamic movement however surged forward politically while still holding on to its military option. These were most of the themes and ideas highlighted in the discussion.
Keywords: الفصائل الفلسطينية -- القضية الفلسطينية -- إعلان القاهرة -- التسوية السلمية -- التفاوض السلمي -- مفاوضات السلام -- النظم السياسية -- الأحوال السياسية -- الفلسطينيون -- الندوات -- الإصلاح السياسي -- الانتخابات الفلسطينية -- السياسة الإسرائيلية